2004
DOI: 10.1111/j.0022-1112.2004.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet reflectivity in three species of Lake Malaŵi rock‐dwelling cichlids

Abstract: The body colouration extending into ultraviolet wavelengths in three species of Lake Malaŵ i rock-dwelling cichlids, Metriaclima zebra, Metriaclima benetos and Metriaclima barlowi was quantified. All three species were ultraviolet reflective with interspecific differences in reflectivity. In addition, individuals were able to behaviourally mediate their reflectivity. # 2004 The Fisheries Society of the British Isles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…[35,36]), and several cichlids can perceive UV light (e.g. [37]), little is known about the role of UV in cichlid visual communication [38].…”
Section: Cellular and Molecular Basis Of Cichlid Colouration And Colomentioning
confidence: 99%
“…[35,36]), and several cichlids can perceive UV light (e.g. [37]), little is known about the role of UV in cichlid visual communication [38].…”
Section: Cellular and Molecular Basis Of Cichlid Colouration And Colomentioning
confidence: 99%
“…Therefore, in contrast to Nile Tilapia, the visual system and indeed other sensory modalities such as olfaction, the mechanoreceptive lateral line system and hearing, may have become more specialized in lake-dwelling cichlid species that have evolved in relatively more stable conditions and tend to utilize specific microhabitats and feeding strategies. Despite increasing interest in the sensory biology of cichlids in recent years, especially with regard to the visual system (e.g., Jordan et al 2004Jordan et al , 2006Parry et al 2005;Carleton et al 2008;Hofmann et al 2009Hofmann et al , 2010, this remains to be tested, but the Great Lakes cichlids and their riverine ancestors provide ample opportunity to investigate the evolution of different sensory strategies.…”
Section: Implications For Visual Ecologymentioning
confidence: 99%
“…Cichlids have diverse visual systems and vision is thought to have played an important role in the explosive radiations of these fishes (Kocher 2004;Hofmann et al 2009Hofmann et al , 2010. Eyes are specifically adapted to the lifestyles of the animals that bear them (Land and Nilsson 2002) and the Great Lakes cichlids have become model systems for the study of the evolution of visual systems, especially in relation to nuptial colour patterns and speciation through sensory drive (Jordan et al 2004(Jordan et al , 2006Parry et al 2005;Maan et al 2006;Carleton et al 2008;Seehausen et al 2008;Hofmann et al 2009Hofmann et al , 2010. Therefore the visual system of the Nile Tilapia is of great interest in relation to the evolution of the visual systems of the Great Lakes cichlids.…”
Section: Introductionmentioning
confidence: 99%
“…Male nuptial colors may also be a signal used between males (Jordan et al 2004;Seehausen and Schluter 2004;Pauers et al 2008;Jordan et al 2010). Pauers et al (2008) found that males show higher levels of aggression toward similarly colored heterospecifics than towards the phylogenetically more closely related, but differently colored, heterospecific males.…”
Section: Introductionmentioning
confidence: 99%